Adaptive Signal Control and Routing using Real-Time Data Processing - Anandan Dhanaraj (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the implementation and impact of adaptive signal control systems enhanced by real-time data processing to solve urban traffic congestion. The article explores how these intelligent traffic management systems dynamically adjust signal timing based on actual traffic conditions rather than predetermined schedules, resulting in significant improvements in urban mobility. The article details the system architecture, incorporating strategic sensor placement, real-time analytics frameworks, and sophisticated control algorithms that enable responsive traffic management. Through analysis of multiple case studies across diverse urban environments, the article demonstrates how adaptive systems consistently outperform conventional approaches, delivering reductions in travel times of 25-40%, decreases in harmful emissions of approximately 18%, and substantial economic benefits with favorable cost-benefit ratios. The article also investigates implementation challenges and emerging technologies, including machine learning enhancements and vehicle-to-infrastructure communication, which promise to revolutionize traffic management further. By synthesizing technical article analysis with performance data from real-world deployments, this article comprehensively examines adaptive signal control’s current capabilities and future potential in creating more efficient, sustainable, and livable urban environments.